Restoration And Preservation of Traditional Water Resources: A Study of Uttarakhand - Meenu Sharma; Nisha Sharma; Ananya Sharma (Westscience Press, 2023)
The essence of all life is water. Without water, nothing on our planet can grow. Traditional water resources, which were once the lifeblood of the Himalayan population, are disappearing alarmingly in Himalayan areas of Uttarakhand. In these steep regions of Uttarakhand, life cannot advance in the correct path without these natural water sources. Traditional water resources provided for many kinds of daily requirements, including drinking, cooking, cleaning, irrigation, and caring for animals. Water is becoming more scarce everywhere in the world, even in the Himalayan region. In an effort to prevent future generations from facing a shortage of potable water, efforts should be made to protect these ancient natural water sources.